SYNTHESIS OF THE TECHNICAL CONTROL SYSTEMS WITH VARIABLE STRUCTURE - I. V. Prokopyev (Научный вестник МГТУ ГА)
Change. Also the object as a result of an adverse effect is considered. The formal problem definition of synthesis of hardy management system is considered. Model choice criteria ensemble is set. The rule of choice algorithm implementation on the basis of different reference functions is provided. The conclusion is drawn that in case of preliminary processing of the available prior data it is possible to select reference functions correctly which reflect physical processes more precisely. The mathematical description of a dynamic object on the basis of a differential equation, or its decision is provided. Definition of function of a trend is given. Criteria for selection of model of damage are given. The recommendation of modification of Demark trends algorithm by means of the sliding Yazvinsky's window and a method of self-organization for increase of accuracy of creation of a predictive model of damage is made. It is offered to realize a model choice by means of more complex logical analysis of an observed vector in the appropriate situation. Logic-functional control task definition is given and approach to its decision is formulated. The conclusion about what the task of synthesis management system consists of is given. This article describes the method of synthesis of control system with variable structure provides increasing survivability control system in a significant change of the external environment, as well as the object itself from the adverse impacts.